Pendampingan Pimpinan Cabang ‘Aisyiyah Sukodono melalui Implementasi Web sebagai Media Informasi dan Layanan Digital - Faozen Faozen; Juhanda Juhanda; Edhi Siswanto; Cristian Rizqi Anggraini (LPkM Universitas Bakrie, 2026)
Digital transformation has become an important requirement for community-based organizations to improve governance and information services. The Sukodono branch of ‘Aisyiyah faced several challenges, including the absence of an integrated information system, limited digital literacy among administrators, and unstandardized activity documentation. This program aimed to enhance the organization’s digital capacity through website development and digital literacy improvement. A needs-based participatory approach was employed with a pre-experimental one-group pretest–posttest design. The activities included digital needs assessment, CMS-based website development, content management training, social media integration, and three months of intensive mentoring. The participants consisted of 18 active administrators. The results show that the organizational website was successfully developed and utilized as a digital information hub, reaching 1,428 users within the first three months. The average digital literacy score increased from 58.1 to 87.2 after the intervention. In addition, content publication frequency improved, and social media integration contributed to increased digital visibility, as reflected in higher follower growth and engagement rates. The implementation of documentation SOPs also improved activity recording consistency from 38% to 100%. These findings indicate that a needs-based and participatory intervention can gradually improve digital capacity and information systems within community organizations. However, the results are limited to a small organizational scope and a relatively short implementation period, suggesting the need for long-term evaluation to assess sustainability.